Effect of Alkalinity Towards the Formation of NaX Zeolite Membranes - Salwa Mohd Nazir, L. (Elsevier Ltd, 2019)
In this study, the effect of solution alkalinity towards zeolite crystallization and growth were investigated for NaX zeolite crystals and NaX zeolite membrane grown via secondary growth. NaX zeolite crystals were synthesized by using different Na2O/Al2O3 ratios of 15, 16, 17, 18 and 19. XRD and FESEM results indicated that Na2O/Al2O3 ratio of 17 and above produced NaX zeolite crystal with high crystallinity ad single phase NaX zeolite. NaX zeolite membrane were also synthesized by varying Na2O/Al2O3 ratios of 17 and 19 in order to study the growth of NaX zeolite membrane via secondary growth. Na2O/Al2O3 ratio of 17 resulted in better intercrystalline growth of the membrane layer compared with the membrane synthesized using mixture solution with Na2O/Al2O3 ratio of 19. Â© 2019 Elsevier Ltd.